Queueing network model with jockeying to reduce the waiting time in the airport. (9th March 2022) - Priya, K. Banu; Kumar, M. Sandeep; Geetha, M.; Prabhu, J.; Maheshwari, V.; Rajendran, Sukumar; Prasanna, M.; Rajendran, P.
The airport queueing network model (AQNM) primary objective is to reduce the congestion and waste the passengers' time in the airport queues, mainly while crossing the checking baggage section, immigration, boarding, and leaving the system. In the AQNM model, every time the passenger notifies, the system moves slowly, and if the queue is multiserver, the passenger can use jockeying among the queues. If the queue is a single server queue, then jockeying is not possible. Additionally, a numerical example has worked with the Monte-Carlo simulation method for queueing theory and MatLab. To show the effect of the presented AQNM model, the results of waiting time without jockeying and waiting time with jockeying has been compared.